1980
DOI: 10.1002/bjs.1800670720
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral carcinoma of the breast

Abstract: Among the 911 cases of carcinoma of the breast treated between 1969 and 1978 there were 39 cases of bilateral primary cancer. Of these, 17 were synchronous tumours defined as cancers diagnosed and treated during the same primary hospital admission. The remaining 22 patients had tumours that were diagnosed separately (metachronous tumours), with a mean time interval of 5 years and 8 months between presentation of first and second primaries (range 6 months to 20 years). Of the metachronous tumours, 20 had presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
3

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 9 publications
(3 reference statements)
4
19
0
3
Order By: Relevance
“…But in these studies, metachronous bilateral disease seemed to entail a prognosis similar to that in unilateral cancer when survival was calculated from the date of the second diagnosis as in our study. The discrepancies between our results and those of the latter studies might have been smaller, however, if they had taken into account both age and disease stage (McCredie et al, 1975;Bailey et al, 1980;Burns et al, 1984) or had used a life-table technique for computing the survival (McCredie et al, 1975). This assumption is suggested by our finding that correction for age alone gave less marked differences between unilateral and bilateral cases.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…But in these studies, metachronous bilateral disease seemed to entail a prognosis similar to that in unilateral cancer when survival was calculated from the date of the second diagnosis as in our study. The discrepancies between our results and those of the latter studies might have been smaller, however, if they had taken into account both age and disease stage (McCredie et al, 1975;Bailey et al, 1980;Burns et al, 1984) or had used a life-table technique for computing the survival (McCredie et al, 1975). This assumption is suggested by our finding that correction for age alone gave less marked differences between unilateral and bilateral cases.…”
Section: Discussionmentioning
confidence: 52%
“…In three other studies (McRedie et al, 1975;Bailey et al, 1980;Burns et al, 1984) it has been observed that patients with synchronous cancers fare badly, while the prognosis for women with metachronous cancers is better. But in these studies, metachronous bilateral disease seemed to entail a prognosis similar to that in unilateral cancer when survival was calculated from the date of the second diagnosis as in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The longer the interval between the diagnoses of the two cases, the better is the survival rate. [7,8,9,10] Optimal surgical management of these primary synchronous breast carcinoma is controversial. In the past these cases were treated more aggressively with bilateral MRMs with the view that the disease has poor survival and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Some believe that this patient's clinical scenario is similar to that of a bilateral breast cancer patient. Generally, it has been recognized that the prognosis of patients with simultaneous bilateral breast cancer is worse than the prognosis of patients with unilateral breast cancer (7)(8)(9)(10)(11)(12). However, some authors have not observed a difference in the survival of patients with bilateral breast cancer and unilateral breast cancer (13,14).…”
Section: Case Reportmentioning
confidence: 99%